Analysis of Land Water Balance to Set The Planting Time of Upland Rice in Kampar District - Asri Dwilika Pratiwi; Besri Nasrul (Soil Science Department, Faculty of Agriculture, Tanjungpura University, 2022)
Upland rice productivity in Kampar has decreased due to inappropriate planting time with rainfall. Plant water needs will not be met during the dry season and are at risk of crop failure. This study aims to determine the level of availability of groundwater based on land water balance analysis and determine the planting time of upland rice. The method used in this research was a survey method. Soil data of bulk density, field capacity water content, permanent wilting point moisture content, soil texture, and C-organic content were obtained with ring and composite soil samples. Soil sampling points were determined based on the results of overlaying the soil map and land use map using GIS techniques. Climate data for the period 1990–2019 was obtained from the Sumatra River Region III Center. Analysis of land water balance was carried out using the Thornthwaite-Matter method. The results showed that Kampar Regency was classified as a wet area with an annual rainfall of 2,508 mm (Oldemann D1). Soil water content was classified as a sufficient criterion every month, except for June–August. The planting of upland rice at SLH 1–SLH 7 (inpago variety) can be done in January, May, and September, while at SLH 8, it is done in January and September. Planting using local varieties at SLH 1–SLH 7 can be done in February and September, while at SLH 8, it is done in March and September. Alternatif planting can also be done by planting inpago varieties in February and local varieties in September.